Gems of hubble : - Mitton, Jacqueline (Cambridge Univ. Press, 1996)
Images from the Hubble Space Telescope are transforming our view of the universe. The planets of our solar system, the birth of stars, the effects of black holes, and remote galaxies are imaged with a clarity that can be achieved by a telescope in space